Strategic Analysis of Aviation Vocational Education Development Using the Ansoff Matrix: A Qualitative Case Study of Politeknik Penerbangan Surabaya - Muhammad Kokon Shandy Shandy; Nur Ismanidar; Fiel Salvador Rangel Da Cunha Braz (Politeknik Penerbangan Surabaya, 2026)
Aviation vocational education institutions must continuously adjust their programs, partnerships, and service portfolios to technological change and evolving industry competence requirements. This study analyzes the strategic development options of Politeknik Penerbangan Surabaya using the Ansoff Matrix. A qualitative case-study design was employed. Data were obtained through semi-structured interviews with purposively selected internal and external stakeholders, direct observation of academic and training activities, and analysis of institutional strategic plans, performance reports, accreditation records, and cooperation documents. The data were analyzed through thematic coding and subsequently mapped to the four Ansoff strategies: market penetration, market development, product development, and diversification. Triangulation and member checking were used to enhance credibility. The findings indicate that product development and market development offer the strongest medium-term combination of feasibility and strategic impact. Priority initiatives include upgrading selected study programs, developing short courses in unmanned aircraft systems, airport operations, rescue and firefighting, and aviation cybersecurity, modernizing laboratories and simulators, and expanding cooperation with aviation organizations in Southeast Asia and the Middle East. Diversification through applied research centers, a digital academy, startup incubation, and professional consulting offers long-term value but requires stronger governance, specialist staff, and sustainable financing. The study is novel in adapting the product-market logic of the Ansoff Matrix to an aviation vocational education context and in proposing a staged institutional growth portfolio. Practically, the findings provide institutional leaders with a risk-sensitive roadmap for strengthening graduate relevance, international reach, innovation capacity, and institutional competitiveness.